External strain effect on the electronic and mechanical properties of the superconductor Nb2InC. (March 2015) - Li, Chenliang; Wang, Chaoying; Zhang, Fengkui; Ma, Decai; Wang, Baolai; Wu, Guoxun
Abstract: We use first-principles method to investigate the effects of external strain ε on the structural, mechanical and electronic properties for the superconductor Nb2 InC. The results show that the tensile strain induces an isostructural phase transition in Nb2 InC. The elastic constants C ij, bulk modulus B, shear modulus G, Young's moduli E, and Poisson ratio v ij of Nb2 InC were also investigated in the range from ε =−10% to ε =10%. It indicates that Nb2 InC is mechanically stable under external strain, and its brittle–ductile transition occurs at ε =3.5%. Moreover, Nb2 InC gets a negative Poisson ratio at ε =4%. The calculated electronic structures indicate that the Nb–C bonding is stronger than Nb–In bonding in Nb2 InC. The energy band structures and densities of states of strained Nb2 InC were also calculated and discussed in detail. From these calculations, it is clear that the related properties of Nb2 InC can be easily tuned by strain. Therefore, our findings are very useful to tailor the physical properties of Nb2 InC by using strain engineering. Highlights: The mechanical properties of Nb2 InC are highly sensitive to external strain. Nb2 InC undergoes an isostructural phase transitions under tensile strain. The transition from the brittle to ductile occurs at ε =−3.5%. The electronic structures of Nb2 InC present obvious change under strain.